Trends and cycles in the Danish economy - Christoffer Jessen Weissert (Danmarks Nationalbank, 2024)
I present empirical results on the contribution of three key drivers of inflation in Denmark: an inflation trend anchored by inflation expectations; the Danish business cycle; and an energy price cycle. All three drivers contribute significantly to the development of inflation and explain most of the variation in the last 40 years. The results are based on a data-driven trend-cycle model estimated over the period from 1985 to 2023. The impact of the cyclical gap on inflation manifests itself via an active and stable Danish Phillips curve relationship. In the context of the Danish economy, the model also provides new estimates of GDP, employment, and unemployment rate gaps, as well as an inflation-relevant activity gap.
Keywords: 330; Inflation; economic situation; business cycle; time series analysis; Denmark; Inflation; Wirtschaftslage; Konjunktur; Zeitreihenanalyse; Theorie; Dänemark